OTOMATISASI IRIGASI SAWAH MENGGUNAKAN SENSOR ELKTRODA LEVEL BERBASIS MIKROKONTROLER ATMEGA8535 - Elly Mufida; Supriyanto S (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
Agriculture is the main source of livelihood of the Indonesian population living in rural lowlands. Land - land that is widely used by villagers to be rice fields. Paddy field where rice growing is derived from cultivated land in the irrigation later. Irrigated rice fields from various sources, which is derived from its own springs and water sources to promote agriculture hujan. Dan one of which is irrigated rice fields automatically, so that it can reduce the risk of excess or lack of water. The advantages of microcontroller-based automatic irrigation equipment compared to conventional irrigation is the owner of paddy rice fields do not need to check whether the excess water or lack of water and can be automatically connected to another device. This makes humans more forward thinking to design automatic irrigation rice fields, where the workings of this tool is quite simple, namely, when the water in the fields excess or shortage of water, then the sensor will automatically send commands to the phone owner via modem (wavecom) in the form of SMS, with a program that has been filled and designed on the microcontroller, then the command will be executed in order to run the system.Keywords: Irrigation System, Microcontroller, SMS, Wavecom